1970
DOI: 10.18388/abp.2010_2401
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sporulation in the yeast Saccharomyces cerevisiae.

Abstract: Sporulation of the budding yeast Saccharomyces cerevisiae — equivalent to gametogenesis in higher organisms, is a complex differentiation program induced by starvation of cells for nitrogen and carbon. Such environmental conditions activate coordinated, sequential changes in gene expression leading to production of haploid, stress-resistant spores. Sporulation comprises two rounds of meiosis coupled with spore morphogenesis and is tightly controlled to ensure viable progeny. This review concerns the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…Many significantly enriched GO terms were clustered into subsets of processes known to be regulated by Hst1 (and to a lesser extent Sir2) at the transcriptional level, and are expected to respond to NAM-induced inhibition of these sirtuins, e.g. sexual reproduction (sporulation) ( 62 , 63 ) and metabolism (‘de novo’ NAD biosynthetic process, sulfur amino acid, carboxylic acid, energy reserve metabolic processes) ( 17 , 18 ) (Table 3 ). GSEA also revealed that transcripts repressed in NAM-treated cells were significantly enriched in ribosome biogenesis, translation and tRNA modification (Supplementary Figure S1, Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Many significantly enriched GO terms were clustered into subsets of processes known to be regulated by Hst1 (and to a lesser extent Sir2) at the transcriptional level, and are expected to respond to NAM-induced inhibition of these sirtuins, e.g. sexual reproduction (sporulation) ( 62 , 63 ) and metabolism (‘de novo’ NAD biosynthetic process, sulfur amino acid, carboxylic acid, energy reserve metabolic processes) ( 17 , 18 ) (Table 3 ). GSEA also revealed that transcripts repressed in NAM-treated cells were significantly enriched in ribosome biogenesis, translation and tRNA modification (Supplementary Figure S1, Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…To test whether the transcripts produced by T7 RNA polymerase were translated, we created diploid strains in which the only source of a1 messages was at HMR T7pro :: a1 . Sporulation requires a1 protein and can proceed with even small amounts present (reviewed in Piekarska et al 2010 ). Such strains were not able to sporulate (0 tetrads among thousands surveyed) in sporulation medium containing galactose and 10 mM nicotinamide to derepress HML and HMR .…”
Section: Resultsmentioning
confidence: 99%
“…A deficiency in glucose and nitrogen are known to induce meiosis followed G1 arrest of the mitotic cell cycle in diploid yeast cells 54 , 55 . When yeast cells starve for essential nutrients, sporulation and meiosis coupled with spore formation is induced 56 . However, absence of any nutritional deficiency in our experimental system indicates that G1 arrest and induction of meiosis are triggered by doxorubicin, which may cause a misperception in glucose sensing.…”
Section: Discussionmentioning
confidence: 99%